Aggregation of molecules is controlled in microdroplets. Issue 91 (17th October 2022) - Basuri, Pallab; Shantha Kumar, Jenifer; Unni, Keerthana; Manna, Sujan; Pradeep, Thalappil
Abstract : Fluorescence microscopy reveals the control of aggregation and de-aggregation of molecules in microdroplets, which is strikingly different from that in the bulk. Abstract : Molecular de-aggregation was observed at the air/water interface of aqueous microdroplets. We probed this phenomenon using dyes such as Rhodamine 6G (R6G), Rhodamine B, acridine orange, and fluorescein, which show aggregation-induced shift in fluorescence. The fluorescence micrographs of microdroplets derived from the aqueous solutions of these dyes show that they are monomeric at the air/water interface, but highly aggregated at the core. We propose that rapid evaporation of the solvent influences the de-aggregation of molecules at the air–water interface of the microdroplets.